Expert System for Identification of Skin Disease in Humans using Naive Bayes Classifier Method on Web - Dinar Nugroho Pratomo; Diyah Utami Kusumaning Putri (Jurnal Informatika: Jurnal Pengembangan IT, 2022)
Expert System Identification of Skin Disease in Human is an application that adopts expert knowledge, in this case, a dermatologist, to identify skin diseases in humans found in Indonesia. This expert system is constructed using a naive bayes classifier. To make the system interface more dynamic and easy to access by anyone, this system is made based on the web. Through this web application, users can consult with a system like an expert to know the skin disease that occurs to the human and find the correct treatment to solve the problems.